3x的平方y+xy-[3x的平方y-4(x的平方y+2分之1xy)]-4x的平方y
1个回答
你是要化简的吧
3x^2y+xy-【3x^2y-4(x^2y+1/2*xy)】-4x^2y
=3x^2y+xy-3x^2y+4x^2y+2*xy-4x^2y
=3xy
相关问题
y分之x的绝对值=3,求(x平方+xy+y平方)分之(x平方-xy+4y平方)
x平方-2xy-3y平方=0可变为(x+y)(x-3y)=0则xy+4y平方分之xy-2y平方的值
(3x平方-4y平方)+[-(x平方-2xy-y平方)]-[(3x平方-2xy-y平方)]
已知;3X的平方+XY-2Y平方=0,求(X-Y分之X+Y)+Y平方-X平方分之4XY)除以X平方-9
3x平方y+{xy-[3x平方y-(4xy平方+1/2xy)]-(4x平方y+3/2xy)}答案是什么
1-x+2y分之x-y除以x的平方+4xy+4y的平方分之x的平方-y平方
3(2x平方y-3xy平方)-(xy平方-3x平方y),其中x=2分之1,y=-1
3X平方+2Xy-4y平方-(3xy-4y平方+3x平方)
(-3x的平方y)(-4x的平方y的平方-5y的立方-6x+1) 3x的平方y(-4x的平方y+2xy的平方-xy)
3x的平方y-(2xy的平方-2(xy-3分之2x的平方y) 2xy)-2x的平方y,